2014
DOI: 10.1093/infdis/jiu611
|View full text |Cite
|
Sign up to set email alerts
|

HIV Nef Promotes Expression of B-Lymphocyte Stimulator by Blood Dendritic Cells During HIV Infection in Humans

Abstract: Dendritic cells (DCs) modulate B-cell survival and differentiation, mainly through production of growth factors such as B lymphocyte stimulator (BLyS; also known as "B-cell factor belonging to the tumor necrosis factor family" [BAFF]). We have recently shown that, in human immunodeficiency virus (HIV)-infected individuals with rapid and those with classic disease progression, B-cell dysregulations were associated with increased BLyS expression in plasma and by blood myeloid DCs (mDCs), in contrast to aviremic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…Moreover, Nef expression in macrophages induces the release of inflammatory factors such as MIP-1a, MIP-1b, IL-6, TNF, and IL-1b, among others (64)(65)(66)(67). Of high relevance to the present work, one study has reported also that recombinant soluble Nef increases BAFF expression in monocyte-derived DCs (28). As the biological effects of recombinant proteins are sometimes dictated by factors such as dosage and purity, we chose a different approach in which MDM cultures were infected with fully replicative molecular clones of HIV-1 that differ only in their expression of Nef.…”
Section: Nef Is Dispensable For Hiv-1-mediated Baff Upregulationmentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, Nef expression in macrophages induces the release of inflammatory factors such as MIP-1a, MIP-1b, IL-6, TNF, and IL-1b, among others (64)(65)(66)(67). Of high relevance to the present work, one study has reported also that recombinant soluble Nef increases BAFF expression in monocyte-derived DCs (28). As the biological effects of recombinant proteins are sometimes dictated by factors such as dosage and purity, we chose a different approach in which MDM cultures were infected with fully replicative molecular clones of HIV-1 that differ only in their expression of Nef.…”
Section: Nef Is Dispensable For Hiv-1-mediated Baff Upregulationmentioning
confidence: 57%
“…The HIV-1 accessory protein Nef was another possible candidate that could have a role in the noticed virus-dependent BAFF secretion in MDMs because of its known capacity to induce production of several soluble factors in monocyte-macrophages (65), including BAFF in mDCs (28). However, our results using a Nef-deleted variant suggest that such virus is still able to upregulate BAFF production in MDMs.…”
Section: Hiv-1-mediated Baff Induction Is Modulated By the Macrophagementioning
confidence: 74%
“…2C) when compared to HIV-infected CSWs. For consistency and comparison with our previously published observations 161819, we have analyzed the minor fraction of CD14 + monocytes which do not express detectable levels of CD11c, separately from the bulk of CD14 + CD11c + monocytes. In fact, when compared to CD14+CD11c- monocytes, CD14+CD11c+ cell percentage greatly fluctuated in HIV+ progressors18, and these cells expressed greater levels of surface BLyS1617.…”
Section: Resultsmentioning
confidence: 89%
“…Indeed, soluble HIV-Nef can directly modulate BLyS membrane expression and soluble release by monocyte derived DCs (mo-DCs)19, and HIV-Env has been shown to upregulate BLyS expression by macrophages24. Furthermore, BLyS has been shown to be directly induced by type I IFNs2526.…”
Section: Discussionmentioning
confidence: 99%
“…BAFF production in innate cells is triggered directly by viral products, including double-stranded RNA (104), negative factor (Nef) (105), and the exterior envelope glycoprotein gp120 (106), and indirectly by type I interferon (IFN) secreted from plasmacytoid DCs in response to viral particles (107,108). Among the HIV molecules, Nef has been reported to induce BAFF expression in human DCs and murine macrophages, but the induction of BAFF expression by Nef is negated if the macrophages are M1 polarized (105,109). The role for gp120 in HIV infection is especially interesting because this glycoprotein not only stimulates BAFF and APRIL expression in monocytes but also engages human tonsillar IgD ϩ B cells through interactions with mannose C-type lectin receptors (MCLRs).…”
Section: Viruses Hivmentioning
confidence: 99%